The Potential for Sovereign Wealth Funds to Exert Influence Through Critical Banks in the Five Smallest EU Member States - Jan Körnert; Thomas Junghanns (Credit and Capital Markets – Kredit und Kapital, 2020)
The financial clout of global sovereign wealth funds (SWFs) is massive, and many of these are controlled by authoritarian regimes. It cannot be ruled out that these funds might take shareholding positions in banks which play key roles in other countries. This paper studies the extent to which SWFs have the potential ability to use shareholdings in critical banks as mechanisms to exert influence on other countries' banking systems, taking a comparative approach in considering the five smallest EU member states: Malta, Cyprus, Estonia, Latvia and Lithuania. The study concludes that SWFs would, in many cases, need to dedicate only a tiny portion of their assets in order to gain significant potential for influence within these countries.
Keywords: G21; G15; 330; Swedbank; SEB; Luminor; Sovereign Wealth Funds; Bank of Cyprus; Bank of Valletta; Critical Infrastructure; Banking Systems; Significant Banks; Mediterranean; Baltics